(untitled) - Marca, David A. (Hoboken, N.J., 2005)
This excellent book offers a discussion of e-business, e-process and e-commerce design, from the standpoint of business adaptability and durability. It defines and maps their complex interrelationships, as well as providing guidance on conducting e-projects. Written from the standpoint of business adaptability and durability, this unique resource offers proven principles for successful e-business, e-process, and e-commerce initiatives, applications and projects. Marca shares with us the principles that have most helped his customers create substantial value, return-on-investment, and end-customer benefits. This guidebook provides unique insights for using the Internet to dramatically improve business processes and complex supply chains. It shows process engineers how to translate business processes into Web pages and then link those Web pages to e-commerce applications. It also gives software designers proven methods for developing e-business and e-commerce applications. And it provides project managers with valuable heuristics for realizing successful e-business and e-commerce initiatives.
Keywords: Electronic commerce,Electronic commerce,Business enterprises,Business planning; Computer networks,Management,Computer networks,Management,Computer networks